Topic modeling in tourism research: a bibliometric study - Valentinus Roby Hananto; Vivine Nurcahyawati; Tutut Wurijanto; Titik Lusiani; Mate Kovacs (Indonesian Journal of Electrical Engineering and Computer Science, 2026)
The application of topic modeling in the tourism domain has become a popular research topic in the last decade. This study aims to provide a comprehensive bibliometric analysis of topic modeling research in tourism over the period 2010 to 2023. The data for this study were sourced from the Scopus database, a widely recognized repository of peer-reviewed literature. The search was restricted to publications published from January 1, 2010, to December 31, 2023, to capture the evolution and current state of this rapidly growing field. Using VOSviewer and SciMAT software to analyze articles in the Scopus database, the study identified key trends, influential authors, and future research directions. This study indicates the growth and development in topic modeling for tourism research, with more than 100 Scopus-indexed papers published annually in 2023 alone. The results of this study show that topic modeling has a wide range of applications in tourism, demonstrating its utility in various contexts to understand tourist behavior and enhance smart tourism initiatives.